The Role of Bhabinkamtibmas through Internal Guidance and Counseling in the Prevention of Drug Abuse in Pandaan Polres District Pasuruan (Indonesian Journal of Police Studies, 2024)
This research is motivated by the drugs abuse that is still fluctuative year by year in Pandaan District, Pasuruan Regency. Bhabinkamtibmas is one of the units in binmas technical function that able to reach the society until its smallest unit. Bhabinkamtibmas promotes its pre emtive function by giving advice through guidance and counseling. So as happened with bhabinkamtibmas in Pandaan Police Sector’s who have the job to do the guidance and counseling in preventing the drugs abuse in Pandaan District Pasuruan Police. Starting from that, the writer conducted a research which has the purpose to identify the description of drugs abuse in Pandaan District with its real condition, to be analyzed about the role of bhabinkamtibmas along with the factors that influence the guidance and counseling activity. The research held by using communication and SWOT analysis theory. The writer also used the role, bhabinkamtibmas, guidance and counseling, and drugs abuse concept in each aspect of the choosen theory in each problem. The writer used qualitative method upported by observation, interview with relative parties, and document study.After that, the writer conduct the data analysis by data reduction, data presentation, and making the conclusion. 2 The writer found that the role of bhabinkamtibmas through guidance and counseling is not maximal yet. Beside that, the lack of personnels, the personel’s education background, also facilities and infrastructure are being the problems for Pandaan Police Sector to achieve the organization’s goal. The suggestions that are given by the writer are it is needed to add the personnels’ quantity, along with the education, training, and increasement of personnels’ capabilities. It is also need to add the facilities and infrastructure to support the tasks’ importance so that the guidance and conseling will be able to be conducted intensively and at the end of the day, can raise the people’s awareness to do the drugs abuse prevention together in Pandaan District Pasuruan Police.
Keywords: BHABINKAMTIBMAS; BIMBINGAN DAN PENYULUHAN